2014
DOI: 10.4236/acs.2014.42021
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Rainfall Events over the Amazon Basin Produce Significant Quantities of Rain Relative to the Rainfall Climatology

Abstract: Although much effort has been made to characterize and understand extreme rainfall's causes and effects, little is known about their frequency and intensity. Moreover, knowledge about their contribution to the total rainfall climatology is still minimal, especially over the Amazon where rainfall data are very scarce. In this paper we propose to classify extreme rainfall events by type and analyze their frequency and intensity over South America with a focus on the Amazon basin. Gridded daily data from the MERG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
4
3
0
Order By: Relevance
“…Pará, Maranhão and Acre State present approximately half of their extensions with similar values. These results partially agree with the increased tendency obtained from Brito et al (2014), which observed the highest values for 1998-2013 in northern Pará and Southern Amazonas State, indicating that the observed patterns should continue in the future. Negative biases of less than 1mm/day were found for NEB in 2071-2100 time-slice (MARENGO AND BERNASCONI, 2015) using CMIP3 HadCM3 data, downscaled by ETA model .…”
Section: Spatial Analysissupporting
confidence: 81%
See 4 more Smart Citations
“…Pará, Maranhão and Acre State present approximately half of their extensions with similar values. These results partially agree with the increased tendency obtained from Brito et al (2014), which observed the highest values for 1998-2013 in northern Pará and Southern Amazonas State, indicating that the observed patterns should continue in the future. Negative biases of less than 1mm/day were found for NEB in 2071-2100 time-slice (MARENGO AND BERNASCONI, 2015) using CMIP3 HadCM3 data, downscaled by ETA model .…”
Section: Spatial Analysissupporting
confidence: 81%
“…The Roraima State, one of the areas highlighted by Brito et al (2014), presents a decrease in the accumulated rainfall for heavy and very heavy events, agreeing with the behavior evaluated by the authors. This pattern was _________________Revista Brasileira de Climatologia_________________ ISSN: 1980-055x (Impressa) Another parameter calculated in this work was the percentage contribution of each type of extreme event to the total amount of rainfall precipitated over the continent.…”
Section: Spatial Analysissupporting
confidence: 75%
See 3 more Smart Citations